Tunneling explains efficient electron transport via protein junctions - Fereiro, Jerry A. (Proc Natl Acad Sci U S A, 2018)
Metalloproteins, proteins containing a transition metal ion cofactor, are electron transfer agents that perform key functions in cells. Inspired by this fact, electron transport across these proteins has been widely studied in solid-state settings, triggering the interest in examining potential use of proteins as building blocks in bioelectronic devices. Here, we report results of low-temperature (10 K) electron transport measurements via monolayer junctions based on the blue copper protein azurin (Az), which strongly suggest quantum tunneling of electrons as the dominant charge transport mechanism. Specifically, we show that, weakening the protein–electrode coupling by introducing a spacer, one can switch the electron transport from off-resonant to resonant tunneling. This is a consequence of reducing the electrode’s perturbation of the Cu(II)-localized electronic state, a pattern that has not been observed before in protein-based junctions. Moreover, we identify vibronic features of the Cu(II) coordination sphere in transport characteristics that show directly the active role of the metal ion in resonance tunneling. Our results illustrate how quantum mechanical effects may dominate electron transport via protein-based junctions.